(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: The characteristics of newly diagnosed patients and the complications of Thalassemia patients diagnosed in childhood who survive into adulthood are often very diverse with different clinical and subclinical charateristics. Objectives: Describe the clinical and the subclinical characteristics of patients with β-Thalassemia at Can Tho Children’s Hospital in 2024. Methods: Retrospective description of 61 pediatric patients diagnosed with β-thalassemia treated at Can Tho Children’s Hospital. Results: 50.8% male and 49.2% female. The age group 5-10 years old accounts for the majority (68.9%). Kinh people make up the majority with 91.8% and 8.2% are Khmer. The most common reason for hospitalization is pallor, accounting for 62.3%. Regarding symptoms, 50.8% of patients had clinical signs of anemia such as pale skin and mucous membranes, 3.3% of patients had jaundice and 8.2% of patients had hepatomegaly and 85.2% of patients had hepatomegaly. % of patients with splenomegaly. Average Hb 6.67 ± 1.03g/dL Hct 22 ± 3.35%. The average MCV index was 72.5 ± 7.58 (fl) and the average MCH was 22.45 ± 3.68 (pg). HbA was 75.92 ± 2.3% and HbF was 2.74 ± 0.6%. The rate of iron overload is 31%. Conclusion: β-Thalassemia disease has diverse clinical manifestations such as clinical and subclinical anemia, decreased Hb and Hct, liver and spleen enlargement.